Identification of potential sources of PM10 pollution from biomass burning in northern Thailand using statistical analysis of trajectories - Praphatsorn Punsompong (2018)
© 2018 Open burning emissions strongly influence smoke haze problems in Southeast Asia (SEA). The main objective of this study is to investigate the percent contribution of emissions from local and transboundary on air pollutant concentrations, particularly PM10(particulate matter with a diameter of less than 10 μm), using the potential source contribution function (PSCF). A three-day backward trajectory (BWT) analysis of air mass movements at the Chiang Mai Air Quality Monitoring (CM-AQM) station in the dry season (February–April) during the years 2010–2015 was run and clustered. It was found that the air masses mainly originated from the southwest of the CM-AQM station. The correlation between the PM10concentration and the number of active fires during the three-day BWT showed the highest correlation in April (R2= 0.64). The PSCF values showed that most of the high-potential sources (0.9–1.0) and emissions were transboundary from Myanmar (73.2%) and within Thailand (26.8%). The major open burning source during March and April was found in the agricultural areas of Myanmar, and the second-greatest source was found in the forested areas of Myanmar. However, the agricultural areas of Thailand contributed to the PM10concentration in northern Thailand (NT) in February. Thus, this result shows that potential point sources of pollutants such as biomass burning, including those transported across national boundaries, can be investigated and determined their locations in the haze episodes of NT.